SARS-CoV-2 variants inactivation of plasma units using a riboflavin and ultraviolet light-based photochemical treatment. (August 2022) - Ferrari, Alessandro; Cassaniti, Irene; Sammartino, Josè Camilla; Mortellaro, Cristina; Del Fante, Claudia; De Vitis, Simona; Barone, Eugenio; Troletti, Daniela; Prati, Federica; Baldanti, Fausto; Percivalle, Elena; Cesare, Perotti
Abstract: Background: Test the ability of Mirasol Pathogen Reduction Technology (PRT, Terumo BCT, Lakewood Co, USA) treatment with riboflavin and ultraviolet light (R + UV) in reducing SARS-CoV-2 infectivity while maintaining blood product quality. Material and methods: SARS-CoV-2 strains were isolated and titrated to prepare cell free virus for plasma units infection. The units were then under treatment with Mirasol PRT. The infectious titers were determined before and after treatment with an in house microtitration assay on Vero E6 cells. Thirty-six plasma pool bags underwent PRT treatment. Results: In all the experiments, the measured titer following riboflavin and UV treatment was below the limit of detection of microtitration assay for all the different SARS-CoV-2 strains. Despite the high copies number detected by RT-PCR for each viral strain after treatment, viruses were completely inactivated and not able to infect VERO E6 cells. Conclusion: Riboflavin and UV light treatment effectively reduced the virus titers of human plasma to the limit of detection in tissue culture, regardless of the strain. These data suggest that pathogen reduction in blood products highlight the safety of CP therapy procedures for critically ill COVID-19 patients, while maintaining blood product quality.